1992
DOI: 10.1128/jb.174.22.7075-7079.1992
|View full text |Cite
|
Sign up to set email alerts
|

Diversity among clinical isolates of Histoplasma capsulatum detected by polymerase chain reaction with arbitrary primers

Abstract: Clinical isolates of the fhngal respiratory and systemic pathogen Histoplasma capsum have been placed in several different classes by using genomic restriction fragent length polymorphisms (RFLPs), but in general have not been distinguished further. We report here that a polymerase chain reaction (PCR)-based DNA fingerprinting method that has been termed arbitrary primer or random amplified polymorphic DNA (RAPD) PCR can distinguish among isolates in a single RF1LP class. In this method, arbitrarily chosen oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 25 publications
2
57
0
1
Order By: Relevance
“…Analysis of our findings showed that the H. capsulatum isolates included in this study had 80 to 100% similarity and that despite this genetic similarity, they could be separated into four to six different genotypes. The primers used for RAPD analysis were chosen based on a previous study (8). Although the choice of other primers with higher discriminatory power could be applied to this study, many arbitrary oligonucleotides can serve as informative primers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of our findings showed that the H. capsulatum isolates included in this study had 80 to 100% similarity and that despite this genetic similarity, they could be separated into four to six different genotypes. The primers used for RAPD analysis were chosen based on a previous study (8). Although the choice of other primers with higher discriminatory power could be applied to this study, many arbitrary oligonucleotides can serve as informative primers.…”
Section: Discussionmentioning
confidence: 99%
“…Broad groupings can be defined using hybridization with the yps3 probe (7), with additional discrimination provided by applying a mitochondrial DNA probe to the same Southern blots (15). Random amplification of polymorphic DNA (RAPD) is capable of revealing individual strain subtypes (8). More recently, another typing method has been described that is based on nucleotide sequence variation in the internal transcribed spacer regions of the rRNA gene, where Indianapolis isolates were classified into four types (4).…”
mentioning
confidence: 99%
“…It has been successfully applied in the genetic differentiation of Salmonella (Tikoo, 2001), E. coli (Renqua-Mangia et al, 2004), A. baumannii (Reboli et al, 1994), S. marcescens (Debast et al, 1995), Proteus mirabilis (Bingen et al, 1993), Enterobacter cloacae (Hou et al, 1997), Haemophilus somnus (Myers et al, 1993), Leptospira species (Ralph et al, 1993), L. pneumophilia (Tram et al, 1990, Van Belkum et al, 1993, B. pseudomallei (Haase et al, 1995, Leelayuwet et al, 2000, Aeromonas salmoniciola (Miyata et al, 1995), Aeromonas hydrophila (Miyata et al, 1995), Vibrio cholerae (Leal et al, 2004), S. aureus (Saulnier et al, 1993), Lactobacillus plantarum (Elegado et al, 2004;Lawrence et al, 1993), Bacillus cereus (Svensson et al, 2004), Listeria monocytogenes (Hiroshi et al, 2007), Candida albicans (Lehmann et al, 1992, Robert et al, 1995, Histoplasma capsulatum (Kersulyte et al, 1992) and Cryptococcus neoformans (Yamamoto et al, 1995). RAPD is highly discriminatory and therefore especially useful in the investigation of short term or local outbreaks of disease.…”
Section: Random Amplified Polymorphic Dna -Rapdmentioning
confidence: 99%
“…(Berg et al, 1994;Kim et al, 1995). RAPD markers distinguished between the cultivated mushroom (Khush et al, 1992) and between clinical the fungal pathogens (Kersulyte et al, 1992). RAPD markers identified different populations and species of arbiscularmycohorizal fungi.…”
Section: Introductionmentioning
confidence: 99%